Correlation Of Science Process Skills On Critical Thinking Skills In Junior High School In Jambi City - Maison, Maison; Darmaji, Darmaji; Kurniawan, Dwi Agus; Astalini, Astalini; Kuswanto, Kuswanto; Ningsi, Aziza Putri (Jurnal Penelitian Fisika dan Aplikasinya (JPFA), 2021)
Teachers need to know how science process skills and students' critical thinking skills are. This study aims to see the relationship between science process skills and critical thinking skills so that teachers can determine the appropriate learning methods to improve science process skills and critical thinking skills. The researcher employed a sample of 58 students from class IX junior high school Adhyaksa 1 Jambi City. The sampling technique in this study using cluster sampling. This study's research design is an associative quantitative research method with a correlational research design. Quantitative analysis uses the SPSS program to find descriptive, normality tests, linearity tests, and correlation tests. The results showed that the significance value obtained was less than 0.05. It was seen that there was a relationship between students' process skills and students' critical thinking abilities